2016
DOI: 10.1002/14651858.cd009002.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids for the treatment of dementia

Abstract: Analysis 1.4. Comparison 1 Omega-3 PUFAs versus placebo, Outcome 4 Older Americans Resources and Services-Instrumental Activities of Daily Living (OARS-IADL) change scores (12 months' follow-up, PP analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 94 publications
0
48
0
4
Order By: Relevance
“…One meta-analysis of six RCTs of duration 3 to 40 months and using 0.l4 to 1.8 g EPA+DHA per day identified a slower rate of cognitive decline in those receiving very long chain n-3 fatty acids (259) . In contrast, a meta-analysis of three RCTs involving 632 participants with mild to moderate Alzheimer's disease and followed for 6, 12 or18 months found no evidence of a benefit from very long chain n-3 fatty acids on any outcome that was assessed (260) . A recent large trial found no effects of very long chain n-3 fatty acids (0.225 g EPA plus 0.8 g DHA daily) over three years on cognitive decline (261) .…”
Section: Neurocognitive Healthmentioning
confidence: 91%
See 1 more Smart Citation
“…One meta-analysis of six RCTs of duration 3 to 40 months and using 0.l4 to 1.8 g EPA+DHA per day identified a slower rate of cognitive decline in those receiving very long chain n-3 fatty acids (259) . In contrast, a meta-analysis of three RCTs involving 632 participants with mild to moderate Alzheimer's disease and followed for 6, 12 or18 months found no evidence of a benefit from very long chain n-3 fatty acids on any outcome that was assessed (260) . A recent large trial found no effects of very long chain n-3 fatty acids (0.225 g EPA plus 0.8 g DHA daily) over three years on cognitive decline (261) .…”
Section: Neurocognitive Healthmentioning
confidence: 91%
“…Interestingly many of these studies are indicative that EPA is more important than DHA, which contrasts with the relative roles of these two fatty acids in very early eye and brain development. Although there may be a role for very long chain n-3 fatty acids in slowing cognitive decline (259) , this has not been well demonstrated (258,260) . There is a clear need for larger, longer and higher quality human trials in this area of research.…”
Section: Neurocognitive Healthmentioning
confidence: 99%
“…Se encontraron mejores resultados en fluidez verbal en el grupo rico en DHA frente al control (p=0,04) no hallándose, por el contrario, diferencias estadísticamente significativas en el grupo rico en EPA (p=0,62) frente al control. Esta disparidad podría deberse a que el DHA es el principal componente de las membranas celulares a nivel central 5 y, teniendo en cuenta que los AGPI w-3 están implicados en la estructura y la función de las fracciones fosfolipídicas de la membrana celular en el cerebro, es posible que desempeñen una función importante en los procesos cognitivos 12 . Sin embargo, Boston y col 21 encontraron mejoría en la clasificación analógica visual del cuidador (p=0,02) suplementando con etil-EPA.…”
Section: Discussionunclassified
“…Examinando los seis estudios seleccionados se encuentran mejores resultados en la cognición global en los que utilizan dosis más bajas (en torno a 500 mg de DHA y EPA) 19,20 que en otros que suplementan con dosis mayores de 1 g [22][23][24] . Aunque no está claro qué dosis de AGPI w-3 es la más adecuada para influir en el rendimiento cognitivo 23 , la mayoría de las guías recomienda una ingesta diaria de 250 a 1000 mg de EPA y DHA para satisfacer los requerimientos de una dieta saludable en adultos 12 . En el estudio de Bun y col 19 en el grupo control también se interviene aunque no sea mediante suplementación ni dieta, sino mediante ejercicio físico, planteando una posible sinergia cara a la prevención de EA.…”
Section: Discussionunclassified
See 1 more Smart Citation